Lopinavir and atazanavir in pregnancy: comparable infant outcomes, virological efficacies and preterm delivery rates. Issue 1 (22nd July 2015) - Perry, MEO; Taylor, GP; Sabin, CA; Conway, K; Flanagan, S; Dwyer, E; Stevenson, J; Mulka, L; McKendry, A; Williams, E; Barbour, A; Dermont, S; et al.
Abstract : Objectives: The aim of the study was to identify differences in infant outcomes, virological efficacy, and preterm delivery (PTD) outcome between women exposed to lopinavir/ritonavir (LPV/r) and those exposed to atazanavir/ritonavir (ATV/r). Methods: A retrospective case note review was carried out. The case notes of 493 women who conceived while on LPV/r or ATV/r or initiated LPV/r or ATV/r during pregnancy and who delivered between 1 September 2007 and 30 August 2012 were reviewed. Data collected included demographics, antiretroviral use, HIV markers, and pregnancy and infant outcomes. Infant outcomes, virological efficacies and PTD rates for LPV/r and ATV/r were compared. Results: A total of 306 women received LPV/r (82 conceiving while on the drug and 224 commencing it post‐conception) and 187 received ATV/r (96 conceiving while on the drug and 91 commencing it post‐conception). Comparing the two protease inhibitors (PIs), viral suppression rates were similar and, in women starting antiretroviral therapy (ART) post‐conception, the median times to first undetectable HIV viral load were not significantly different ( P = 0.64). PTD rates did not differ by therapy overall (ATV/r, 13%; LPV/r, 14%) or when considering the timing of first exposure (conceiving on ART, P = 0.81; commencing ART in pregnancy, P = 0.08). Poor fetal outcomes were very uncommon. There were two transmissions, giving a mother‐to‐child transmission (MTCT) rate of 0.4% (95% confidence interval 0.05–1.5%). Conclusions: Both ART regimens were well tolerated and successful in preventing MTCT. No significant differences in tolerability or in pregnancy or infant outcomes were observed, which supports the provision of a choice of PI in pregnancy.